DNA methylation profiling at base-pair resolution reveals unique epigenetic features of early-onset colorectal cancer in underrepresented populations - Jason Sheng Li; Karen Riggins; Li Yang; Chaorong Chen; Patricia Castro; Wedad Alfarkh; Neda Zarrin-Khameh; Michael E. Scheurer; Chad J. Creighton; Benjamin Musher; Wei Li; Lanlan Shen (Clinical Epigenetics)
Abstract Background The incidence of early-onset colorectal cancer (EOCRC) has been rising at an alarming rate in the USA, and EOCRC disproportionately affects racial/ethnic minorities. Here, we construct comprehensive profiles of EOCRC DNA methylomes at base-pair resolution for a cohort of Hispanic and African American patients. Results We show the epigenetic landscape of these EOCRC patients differs from that of late-onset colorectal cancer patients, and methylation canyons in EOCRC tumor tissue preferentially overlapped genes in cancer-related pathways. Furthermore, we identify epigenetic alterations in metabolic genes that are specific to our racial/ethnic minority EOCRC cohort but not Caucasian patients from TCGA. Top genes differentially methylated between these cohorts included the obesity-protective MFAP2 gene as well as cancer risk susceptibility genes APOL3 and RNASEL. Conclusions In this study, we provide to the scientific community high-resolution DNA methylomes for a cohort of EOCRC patients from underrepresented populations. Our exploratory findings in this cohort highlight epigenetic mechanisms underlying the pathogenesis of EOCRC and nominate novel biomarkers for EOCRC in underrepresented populations.